Salomón Usque y la primera traducción castellana del Canzoniere - Canals Piñas, Jordi (Cuadernos de Filología Italiana, 2005)
Analysis of the tipographic characteristics of the volume in which Nicoló Bevilacqua, a printer from Trento who worked in Venice, published the Spanish version of the first part of the Canzoniere of Petrarca in 1567. Salomón Usque, who has been related to Ferrara and Venice’s marranos communities, is the author of this version. Through the words of its brief dedication, as well as the preface signed by Alfonso de Ulloa, we can see Usque´s intentions and the translation theory which lies in his work. Theory that, on the other hand, is opposed to Enrique Garcés’ (1591) and Francisco Trenado de Ayllón’s (1595).